Serum POP concentrations are highly predictive of inner blubber concentrations at two extremes of body condition in northern elephant seals. (November 2016) - Peterson, Michael G.; Peterson, Sarah H.; Debier, Cathy; Covaci, Adrian; Dirtu, Alin C.; Malarvannan, Govindan; Crocker, Daniel E.; Costa, Daniel P.
Abstract: Long-lived, upper trophic level marine mammals are vulnerable to bioaccumulation of persistent organic pollutants (POPs). Internal tissues may accumulate and mobilize POP compounds at different rates related to the body condition of the animal and the chemical characteristics of individual POP compounds; however, collection of samples from multiple tissues is a major challenge to ecotoxicology studies of free-ranging marine mammals and the ability to predict POP concentrations in one tissue from another tissue remains rare. Northern elephant seals ( Mirounga angustirostris ) forage on mesopelagic fish and squid for months at a time in the northeastern Pacific Ocean, interspersed with two periods of fasting on land, which results in dramatic seasonal fluctuations in body condition. Using northern elephant seals, we examined commonly studied tissues in mammalian toxicology to describe relationships and determine predictive equations among tissues for a suite of POP compounds, including ΣDDTs, ΣPCBs, Σchlordanes, and ΣPBDEs. We collected paired blubber (inner and outer) and blood serum samples from adult female and male seals in 2012 and 2013 at Año Nuevo State Reserve (California, USA). For females (N = 24), we sampled the same seals before (late in molting fast) and after (early in breeding fast) their approximately seven month foraging trip. For males, we sampled different seals before (N = 14) and after (N = 15) their approximately four month foraging trip. We observed strong relationships among tissues for many, but not all compounds. Serum POP concentrations were strong predictors of inner blubber POP concentrations for both females and males, while serum was a more consistent predictor of outer blubber for males than females. The ability to estimate POP blubber concentrations from serum, or vice versa, has the potential to enhance toxicological assessment and physiological modeling. Furthermore, predictive equations may illuminate commonalities or distinctions in bioaccumulation across marine mammal species. Graphical abstract: Highlights: Serum was a strong predictor of inner blubber for DDTs, PCBs, CHLs, and PBDEs. Relationships between serum and outer blubber were stronger for males than females. Higher blubber/serum partitioning coefficients in early breeding than late molting. Predictive equations provided for seals at two extremes of body condition. Abstract : Relationships among serum and blubber layers in elephant seals, after fasting and foraging periods, can enhance contaminant studies and enable comparisons among species.